Atividade física de policiais militares durante o radiopatrulhamento no centro da cidade de São Paulo - Santos, Leandro Porto Dos (2020)
Inactivity or low physical activity correlates with the development of obesity and metabolic syndrome. We determined the level of physical activity of the military police officers on patrol radio, day (14 volunteers), and night (12 volunteers), in the center of the city of São Paulo. We assessed the level of physical activity using a Yamax Digi Walker SW 700 pedometer. We measured the waist-hip ratio (WHR), body mass index (BMI), body mass (Kg), absolute fat mass (Kg), fat-free mass (Kg), skeletal muscle mass (Kg), and visceral adipose tissue weight (Kg). We used an impedance scale (SECA 515 mBCA). Systolic (SBP), diastolic (DBP), and mean arterial (MAP) blood pressure (mmHg) were determined. Glucose (mg/dL), glycated hemoglobin - Hb A1c (percentage), insulin (μU/mL), HDL cholesterol (mg/dL), triglycerides (mg/dL) and C reactive protein (mg/dL) were determined in the blood. Insulin resistance was estimated using the HOMA index. Visceral adipose tissue mass (3.95±0.55 for diurnal and 2.38 ± 0.18 for nocturnal, mean ± SEM, p <0.004), plasma insulin concentration (23.97 ± 4.74 for diurnal period and 16.5 ± 7.35 for nocturnal, p <0.03) and systolic blood pressure (day 134.78 ± 3.38 for diurnal period and 121.58 ± 4.01 nocturnal, p <0.01) were different between the nocturnal and diurnal working groups. The results of the level of physical activity during the working period led us to divide the policemen into group 1 (600-2,000 steps), group 2 (2,001-8,000 steps), and group 3 (above 8,000 steps). There was no difference in the number of steps taken by police officers between diurnal and nocturnal working volunteers. The number of steps taken by military policemen during the working period (5045 ± 603) indicates that the majority is physically not very active. BMI was higher in the 600-2000 group compared to the 2001-8000 group 2. Fat-free mass, skeletal muscle mass, HDL-cholesterol in plasma, and DBP were higher in the group 1 (600-2000 steps) compared to the others. The service length period of the policemen in the Corporation was determined. We separated the volunteers into group 1 (1-10 years), group 2 (11 to 19 years), and group 3 (above 19 years). SBP and absolute fat mass were higher in the group with more than 19 years in the Corporation concerning the others. Body mass, BMI, and MAP were higher in the group over 19 years compared to group 1-10. Seventeen of the 26 volunteers have metabolic syndrome; therefore, 65%. Low physical activity during the working hours might contribute to these findings.